Does hand-eye coordination have a relationship with volleyball top passing? - Wahyudi, Ibnu; Sacko, Makan; Sorifah, Sorifah (Universitas Tanjungpura, 2023)
Volleyball game is one of the sports that is used as a tool for physical education and mental development in accordance with national education goals. However, the implementation has not lived up to expectations. This study aims to prove the relationship between eyehand coordination with passing skills in volleyball games. The population in this study was class X SMA Negeri 4 Timpuk, Sekadau Regency. Perposive sampling technique in order to obtain 47 samples. Data analysis in the study was assisted by the SPSS application. The results showed a significance value of 0.005 <0.05, so there was a significant relationship. The conclusion of eye-hand coordination with the ability to pass on volleyball games has a significant relationship.